Financial Management Practices in Malaysian Islamic Social Enterprises (ISE) - Muhammad Iqmal Hisham Kamaruddin; Sofiah Md Auzair; Saunah Zainon (Accounting Research Institute (ARI), UiTM, 2024)
Indexed by SCOPUS/MYCITE